AI and Ethics When Human Beings Collaborate With AI Agents - Cañas, José J. (Frontiers in Psychology, 2022)
The relationship between a human being and an IA system has to be considered as a collaborative process between two agents during the performance of an activity. When the collaboration is between two people, a fundamental characteristic of that collaboration is that there must be co-supervision in which each agent supervises the actions of the other. Such supervision ensures that the activity achieves its objectives, but it also means that responsibility for the consequences of the activity is shared. If there is no co-supervision neither collaborator can be held co-responsible for the actions of the other. When the collaboration is between a person and an IA system, co-supervision is also necessary to ensure that the objectives of the activity are achieved, but it also means that there is co-responsibility for the consequences of those activities. Therefore, if each agent's responsibility for the consequences of the activity is to depend on the effectiveness and efficiency of the supervision that each actor perform of the other agent’s actions, it will be necessary to take into account how that supervision is carried out and the factors on which it depends. In the case of human supervision of the actions of the IA system, there is a wealth of empirical research and theoretical models that can help us to establish cognitive and non-cognitive boundaries and their relationship to human responsibility in collaboration with the IA. There is also empirical research and theoretical models on how an external observer supervise and evaluates human actions. This research and theoretical models can be used to programme AI systems in such a way that the boundaries of responsibility of AI systems can be established. In this paper, we will be proposed how such research and theoretical models on the task of supervising the actions of another agent can be used to establish lines of shared responsibility between a human being and an AI system. The paper will set out to develop a methodology for assessing responsibility based on the results of the collaboration between human and AI agents during the performance in one common activity.